1998
DOI: 10.1076/ceyr.17.12.1150.5129
|View full text |Cite
|
Sign up to set email alerts
|

Fourth module of Xenopus interphotoreceptor retinoid-binding protein: activity in retinoid transfer between the retinal pigment epithelium and rod photoreceptors

Abstract: The results indicate a low but significant activity of IRBP's fourth module in reactions relevant to retinoid exchange.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…Although the IRBP and serum albumin proteins that we have used are from bovine, the mammalian and amphibian IRBPs are homologous (58,59). This is particularly relevant in considering the implications of the results for the physiological concentrations of the carriers.…”
Section: Discussionmentioning
confidence: 99%
“…Although the IRBP and serum albumin proteins that we have used are from bovine, the mammalian and amphibian IRBPs are homologous (58,59). This is particularly relevant in considering the implications of the results for the physiological concentrations of the carriers.…”
Section: Discussionmentioning
confidence: 99%
“…Each module contains roughly 300 amino acid residues distributed into two domains, A and B (Dettai and Lecointre, 2008). The individual modules appear to represent functional units of the protein (Baer et al, 1998a; Gonzalez-Fernandez et al, 1998; Gonzalez-Fernandez et al, 2007; Gross et al, 2000; Loew et al, 2001; Nickerson et al, 1998). X-ray crystallographic and site-directed mutagenesis studies of Xenopus apo IRBP-module 2 (x2) have identified a novel hydrophobic cavity within domain A (Gonzalez-Fernandez et al, 2009), and a hydrophobic cleft in domain B.…”
Section: Introductionmentioning
confidence: 99%
“…To examine this possibility directly, we tested whether ath5 induced the expression of other photoreceptor-specific genes and whether the transdifferentiating cells, when provided a more adhesive substratum, would develop morphologies typical of photoreceptor cells. Characteristic photoreceptor-specific genes include IRBP, which plays an important role in recycling and/or regeneration of retinoid (Gonzalez-Fernandez et al, 1998); the gene encoding the red pigment, a hallmark of cones that sense red light; and rhodopsin, a hallmark of rods. Whereas IRBP expression begins early during photoreceptor differentiation, genes encoding photopigments are expressed during late phases of photoreceptor development (Bruhn and Cepko, 1996); thus, their expression would indicate that ath5 triggered the expression of genes associated with photoreceptor differentiation.…”
Section: Induction Of Rpe Transdifferentiation Toward Photoreceptor Cmentioning
confidence: 99%